2011
DOI: 10.3945/jn.110.136143
|View full text |Cite
|
Sign up to set email alerts
|

Essential Amino Acids Regulate Both Initiation and Elongation of mRNA Translation Independent of Insulin in MAC-T Cells and Bovine Mammary Tissue Slices

Abstract: Current nutrient requirement models assume fixed efficiencies of absorbed amino acid (AA) conversion to milk protein. Regulation of mammary protein synthesis (PS) potentially violates this assumption by changing the relationship between AA supply and milk protein output. The objective of this study was to investigate the effects of essential AA (EAA) and insulin on cellular signaling and PS rates in bovine mammary cells. MAC-T cells were subjected to 0 or 100% of normal EAA concentrations in DMEM/F12 and 0 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
110
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(124 citation statements)
references
References 49 publications
10
110
4
Order By: Relevance
“…On the other hand, there is increasing evidence that Ox-LDL induces beta cell dysfunction and reduction of insulin production (Maziere et al 2004, Abderrahmani et al 2007, Favre et al 2011. Considering the role of insulin in stimulating protein synthesis in mammary gland (Mackle et al 2000, Molento et al 2002, Menzies et al 2009, Appuhamy et al 2011, it can be hypothesized that Ox-LDL may decrease protein synthesis by reducing insulin production in beta cells and its signalling in mammary cells. OLR1, as a major receptor for Ox-LDL, is able to remove Ox-LDL from circulating blood and as a result reduces its deleterious effect on insulin production and signalling.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is increasing evidence that Ox-LDL induces beta cell dysfunction and reduction of insulin production (Maziere et al 2004, Abderrahmani et al 2007, Favre et al 2011. Considering the role of insulin in stimulating protein synthesis in mammary gland (Mackle et al 2000, Molento et al 2002, Menzies et al 2009, Appuhamy et al 2011, it can be hypothesized that Ox-LDL may decrease protein synthesis by reducing insulin production in beta cells and its signalling in mammary cells. OLR1, as a major receptor for Ox-LDL, is able to remove Ox-LDL from circulating blood and as a result reduces its deleterious effect on insulin production and signalling.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 consists of mTOR, regulatory associated protein of TOR (Raptor), and a G protein β subunit-like protein (GβL) (Kim, 2009). A great deal of evidence indicated that P-mTOR at Ser 2448 was an indicator of mTOR pathway activity in immortalized bovine mammary epithelial cells (MAC-T) (Appuhamy et al, 2011b;. Prizant and Barash (2008) showed that P-mTOR in Ser 2448 was completely inhibited by His supplementation, but phosphorylation of the ribosomal protein S6 kinase 1 (S6K1) and eukaryotic initiation factor 4E binding protein (4EBP1) could still be detected.…”
Section: Introductionmentioning
confidence: 99%
“…When 4EBP1 was unphosphorylated, cap-dependent translation was inhibited by competitively blocking the binding of eukaryotic translation initiation factor 4G (eIF4G) to eIF4E (Gingras et al, 1999;Harris and Lawrence, 2003). The elongation step of mRNA translation was enhanced by eukaryotic elongation factor 2 (eEF2) (Wang and Proud, 2006) and was inhibited by its phosphorylation on Thr 56 , which suggested that eEF2 may be a limiting factor in milk protein synthesis (Christophersen et al, 2002;Appuhamy et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this well-known function, in recent years, studies have found that Lys is also an important regulator of various signaling pathways, cell growth, and protein synthesis (Appuhamy et al, 2011a;Lu et al, 2013). In this study, after treatment with 1.2 mM Lys for 24 h, the expression of CSN2 in DCMECs and cell viability were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the transcriptional process of milk protein synthesis is known to be regulated by prolactin through the JAK/STAT5 signaling pathway just as its translational process is regulated by amino acids through the mTOR/S6K1 signaling pathway (Yang et al, 2000b;Galbaugh et al, 2006;Jankiewicz et al, 2006;Wang and Proud, 2006;Prizant and Barash, 2008;Toerien et al, 2010). The activity of mTOR also appears to be modulated by branched-chain amino acids (AA) (Kimball and Jefferson, 2006;Moshel et al, 2006), and the availability of amino acids is the main limiting factor for milk protein synthesis (Reynolds et al, 1994;Appuhamy et al, 2011a), and according to previous reports, lysine and methionine were the most limiting in bovine mammary glands (Bequette et al, 1998;Hanigan et al, 2002). In addition, many previous reports have shown that lysine, as the most limiting, could modulate mammary protein synthesis (Vyas and Erdman, 2009;Appuhamy et al, 2011b;Lee et al, 2012;Wang et al, 2012;Nan et al, 2014;Paz and Kononoff, 2014).…”
Section: Introductionmentioning
confidence: 98%